2013
DOI: 10.1177/0218492312466751
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart surgery outcome analysis: Indian experience

Abstract: The study shows that the Aristotle Basic Complexity score, the Risk Adjustment for Congenital Heart Surgery category, and the Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality category are tools of case mix stratification to analyze congenital heart surgery outcomes in a subset of the Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[18,19] The unique problems encountered by the pediatric surgical teams in developing countries [17,20,21] could explain this higher mortality. Vasdev et al [22] analyzed 1312 CHS at a single Indian center for predictive abilities of ABC, RACHS and STS-EACTS MS scoring systems. They observed 6.85% mortality with RACHS-1 and STS-EACTS MS having better c-indices (0.76 and 0.75 respectively) compared to ABC (0.66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] The unique problems encountered by the pediatric surgical teams in developing countries [17,20,21] could explain this higher mortality. Vasdev et al [22] analyzed 1312 CHS at a single Indian center for predictive abilities of ABC, RACHS and STS-EACTS MS scoring systems. They observed 6.85% mortality with RACHS-1 and STS-EACTS MS having better c-indices (0.76 and 0.75 respectively) compared to ABC (0.66).…”
Section: Discussionmentioning
confidence: 99%
“…They observed 6.85% mortality with RACHS-1 and STS-EACTS MS having better c-indices (0.76 and 0.75 respectively) compared to ABC (0.66). [22] They applied ROC-AUC analysis for the comparison. ROC-AUC fails to segregate subjects in terms of occurrence of the event.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [16] have reported that a low T3 level was an independent predictor of ICU mortality, which is consistent with our finding. However, for CHD patients, especially children, RACHS-1 scores could predict ICU mortality, length of ICU stay and duration of MV [17][18][19][20]. In our study, compared with survivors, non-survivors had higher RACHS-1 scores.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies 16 have reported that low T3 was an independent predictor of ICU mortality, which is consistent with our nding. However, for CHD patients, especially children, RACHS-1 scores could predict ICU mortality, length of ICU stay and duration of MV [17][18][19][20] . In our study, compared with survivors, non-survivors had a higher RACHS-1 score.…”
Section: Discussionmentioning
confidence: 99%